2014
DOI: 10.1186/1471-2164-15-1108
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq gene expression profiling of HepG2 cells: the influence of experimental factors and comparison with liver tissue

Abstract: BackgroundHuman hepatoma HepG2 cells are used as an in vitro model of the human liver. High-throughput transcriptomic sequencing is an advanced approach for assessing the functional state of a tissue or cell type. However, the influence of experimental factors, such as the sample preparation method and inter-laboratory variation, on the transcriptomic profile has not been evaluated.ResultsThe whole-transcriptome sequencing of HepG2 cells was performed using the SOLiD platform and validated using droplet digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
1
30
0
2
Order By: Relevance
“…de la Roche, Ibrahim, Mieszczanek, & Bienz () reported that the expression levels of LEF1 and BCL9L determined the response of IWR‐1 and XAV939 to β‐catenin‐dependent transcriptional activity in chronic Wnt signaling‐activated cells. However, a recent RNA‐seq experiment showed that the elevated expression of these genes was not observed in HepG2 cells compared with normal liver tissue (Tyakht et al, ). In agreement with their observation, our RT‐qPCR experiment detected relatively lower expression of LEF1 in HepG2 cells compared with that in SW480 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…de la Roche, Ibrahim, Mieszczanek, & Bienz () reported that the expression levels of LEF1 and BCL9L determined the response of IWR‐1 and XAV939 to β‐catenin‐dependent transcriptional activity in chronic Wnt signaling‐activated cells. However, a recent RNA‐seq experiment showed that the elevated expression of these genes was not observed in HepG2 cells compared with normal liver tissue (Tyakht et al, ). In agreement with their observation, our RT‐qPCR experiment detected relatively lower expression of LEF1 in HepG2 cells compared with that in SW480 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they utilized a mutant reporter plasmid (pTK56Sac 7 ) in which the wild-type TCF/LEF-binding motif, AACAAAG, was replaced by CCGCGGT, as a negative control (van de Wetering, Oosterwegel, Dooijes, & Clevers, 1991). An improved TCF/LEF reporter plasmid termed TOPFLASH was developed with repeated TCF-binding motifs and a versatile luciferase gene, and the control plasmid containing the mutated motifs was termed FOPFLASH (Korinek et al, 1997;van de Wetering et al, 1997). Chen et al (2009) established mouse L cells that stably express the TCF/LEF reporter gene and Wnt-3a, and used them to screen a chemical library of approximately 200,000 compounds.…”
mentioning
confidence: 99%
“…Variance in expression of a given gene that was not explained by method of separation or by cell type was categorized as 'residual'. On average, 65.3% of transcriptome-wide variance is explained by residual factors, which could include parameters such as the duration and method of trituration [36][37][38] . This number goes down to 53.6% when only analyzing genes found in all datasets ( Supplementary Fig.…”
Section: ݀ ҧmentioning
confidence: 99%
“…Nonetheless, correlations across such samples remain reasonable (i.e. global transcriptomic profiles remain largely intact; Tyakht et al, 2014), and within-protocol (between sample) fold change estimates are thought to be robust to platform bases (i.e. differential expression analysis within a uniform protocol remains a viable assay (Toedling et al, 2012).…”
Section: Leaf Tissue Collection and Rna Sequencingmentioning
confidence: 99%